2017
DOI: 10.1016/j.ijhydene.2017.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sorption properties of Li x Na 1−x MgH 3 (x = 0, 0.2, 0.5 & 0.8)

Abstract: The synthesis, thermodynamic destabilisation and hydrogen absorption/desorption characteristics of the Li x Na 1-x MgH 3 system with (x=0, 0.2, 0.5 and 0.8 molar ratios) have been investigated. Samples were mechanically milled under argon for 5 hours; then characterised by X-ray diffraction (XRD), differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA). Diffraction peaks of NaMgH 3 phase shifted to higher angles and lattice parameters decreased due to the Li addition into the system. 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
2
11
1
Order By: Relevance
“…In particular, NaMgH 3 , which crystalizes in the orthorhombic GdFeO 3 -structure type [12], has been found to have high gravimetric (6 wt%) and volumetric (88 kg m −3 ) hydrogen densities, and exhibiting reversible hydrating and dehydrating reactions [10,11]. The substitution of Na by Li in NaMgH 3 changes the thermodynamic properties of this material and causes the decrease of the unit cell parameters as reported by many authors [1,[13][14][15][16]. However, in the recent work of Vasquez et al [16] on the destabilization and hydrogen absorption and desorption of Li x Na 1−x MgH 3 ( x = 0, 0.2, 0.5 and 0.8), it is found that for x = 0.8 the sample exhibited a different behavior; the unit cell volume instead of decreasing it increases.…”
Section: Introductionmentioning
confidence: 75%
“…In particular, NaMgH 3 , which crystalizes in the orthorhombic GdFeO 3 -structure type [12], has been found to have high gravimetric (6 wt%) and volumetric (88 kg m −3 ) hydrogen densities, and exhibiting reversible hydrating and dehydrating reactions [10,11]. The substitution of Na by Li in NaMgH 3 changes the thermodynamic properties of this material and causes the decrease of the unit cell parameters as reported by many authors [1,[13][14][15][16]. However, in the recent work of Vasquez et al [16] on the destabilization and hydrogen absorption and desorption of Li x Na 1−x MgH 3 ( x = 0, 0.2, 0.5 and 0.8), it is found that for x = 0.8 the sample exhibited a different behavior; the unit cell volume instead of decreasing it increases.…”
Section: Introductionmentioning
confidence: 75%
“…CaH 2 is produced from the reaction of hydrogen release in both dopant-free and doped NaCaH 3 systems. To completely decompose these hydrides into metals and hydrogen molecules, two-step reactions and experimental conditions for temperature/pressure are necessary. , …”
Section: Resultsmentioning
confidence: 99%
“…A high temperature is required for releasing molecular hydrogen from light perovskite-type hydrides . Komiya et al synthesized NaMgH 3 , KMgH 3 , and RbMgH 3 hydrides via a ball-milling method and found that different hydrides have different decomposition pathways at temperatures ranging between 673 and 723 K. Doping suitable elements is strategic to help the dehydrogenation process for most hydrides, making hydrides unstable. In comparison with NaMgH 3 , Na 0.9 K 0.1 MgH 3 experimentally exhibited enhanced dehydrogenation performance owing to its reduced structural stability. The temperature for releasing hydrogen from the NaMgH 3 system was reduced from 580 to 328 K after introduction of K 2 TiF 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Some of the compounds of this structural group are CaCoH 3 , CaNiH 3 , LiTH 3 (T: Fe, Co, Ni, Cu), SrPdH 3 , and SrLiH 3 . ABH 3 perovskite‐type hydrides have been studied in recent years with regard to experimental and theoretical methods to get detailed information about their possible applications . The hydrogen storage techniques should satisfy some necessary conditions like suitable gravimetric and volumetric hydrogen storage capacities, reversibility, and good kinetics in order to get a suitable hydrogen storage material.…”
Section: Introductionmentioning
confidence: 99%
“…In this point of view, hydrogen has gained popularity as abundant, efficient, and sustainable energy source in addition to environmental issues . The works have been directed to produce a clean energy form based on hydrogen as an alternative to carbon‐based products and research interest has concentrated on transportation and storage methods for commercial applications . Apart from elementary water electrolysis, environmentally friendly production processes, that use also renewable energy sources, have been focus of the hydrogen production technologies .…”
Section: Introductionmentioning
confidence: 99%